2015
DOI: 10.1159/000375452
|View full text |Cite
|
Sign up to set email alerts
|

Bavachalcone-Induced Manganese Superoxide Dismutase Expression through the AMP-Activated Protein Kinase Pathway in Human Endothelial Cells

Abstract: Mitochondrial oxidative stress has been suggested as a major etiological factor in cardiovascular diseases. Manganese superoxide dismutase (MnSOD) is an essential antioxidant mitochondrial enzyme. Although polyphenols can induce MnSOD expression, their mechanism of action remains unclear. We examined the effect of bavachalcone, a bioactive compound isolated from Psoralea corylifolia, on MnSOD protein expression and explored whether this effect is mediated through the AMP-activated protein kinase (AMPK) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Our results demonstrated that bavachalcone not only prevents endothelial cells senescence [56,57], but also promotes differentiation of bone marrow stem cells and endothelial progenitor cell via EPO/AMPK pathway (our unpublished data). Effects of kidney-nourishing herbs on differentiation of bone marrow mesenchymal stem cells also have been reported recently.…”
Section: Reinforcing Kidney Drugs and Diseasessupporting
confidence: 63%
“…Our results demonstrated that bavachalcone not only prevents endothelial cells senescence [56,57], but also promotes differentiation of bone marrow stem cells and endothelial progenitor cell via EPO/AMPK pathway (our unpublished data). Effects of kidney-nourishing herbs on differentiation of bone marrow mesenchymal stem cells also have been reported recently.…”
Section: Reinforcing Kidney Drugs and Diseasessupporting
confidence: 63%
“…Our results show that bavachalcone activates ROR α 1 luciferase reporter activity and mRNA and protein expression. Our previous findings show that bavachalcone activates AMPK activity and induces MnSOD expression [ 14 ]. In addition, ROR α 1 activates AMPK activity [ 17 , 18 ], and reduces oxidative stress through the induction of MnSOD and GPx1 expression [ 9 ]; our results are consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a strong inhibitory effect of bavachalcone against 2 important isoforms of UDP-glucuronosyltransferases (UGT), UGT1A1, and UGT1A7, was observed [ 13 ]. In a previous study, we found that bavachalcone activates AMPK kinase activity, promotes the expression of MnSOD, and reduces mitochondrial superoxide anion [ 14 ]. On drug screening, bavachalcone enhances ROR α 1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 is known to reduce inflammation, possess anti-atherosclerosis activity, inhibit cardiomyocyte apoptosis and telomere shortening, resist myocardial oxidative stress damage and myocardial remodeling, maintain myocardial energy balance, and promote autophagy (7). AMPK can inhibit cell proliferation by affecting the cell cycle and metabolism when myocardial and vascular smooth muscle cells are stimulated by ischemia/hypoxia or cardiovascular active substances, playing an important role in the cardiovascular system (10,11). However, it remains unelucidated whether or not the cardiovascular protection of CR is mediated through the SIRT1/ AMPK/mTOR pathway Therefore, we aimed to observe the effects of different energy diets on the myocardial SIRT1/AMPK pathway and provide theoretical basis for the cardiovascular protective effects of CR.…”
mentioning
confidence: 99%